Factors affecting Malaysian English Language teachers’ understanding of feedback - Razali, Khairil Azwar; Abdul Rahman, Zainurin; Othman, Joharry; Sheikh Ahmad, Ismail; Ramdzan Ali, Al Amirul Eimer (Universiti Putra Malaysia Press, 2021)
Within the ESL classrooms, teachers’ written corrective feedback has always been under scrutiny as the inconclusive debate is still going on since the publication of Truscott’s (1996) article that sparked the debate. Moreover, research findings point to Malaysian students’ lacking writing skills which could be attributed to the teachers’ failure to follow the process-based approach and to provide effective feedback in their teaching of writing. This study seeks to find out the factors affecting Malaysian ESL teachers’ understanding of feedback. Data were collected using the Teachers Conception of Feedback (TCoF) Inventoryadapted from Harris and Brown (2008). The questionnaires were sent out to all secondary schools in Pahang, and a total of 372 English Language teachers answered the survey. The data were analysed using SPSS (Version 27) and Exploratory Factor Analysis. From the analysis, five factors were found, namely (i) Purpose, (ii) Peer and Self-assessment, (iii) Teacher, (iv) Attitudes, and (v) Praise. The results are discussed, and recommendations for further research are made. The results of this study are significant in the sense that they could help the country’s policy makers, especially at the Education Ministry level, where better trainings could be delivered to pre-service and in-service teachers so that they are better equipped in delivering top quality education to the future generations.